IMPLEMENTATION PF POVERTY REDUCTION BASED ON ENTERPRISE EMPOWERMENT SMALL AND MEDIUM ENTERPRISES (MSMEs) IN SUKABUMI CITY - Khania Safitri; Dine Meigawati; Andi Mulyadi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
The title of this research is